MODEL DEEP LEARNING UNTUK PEMBELAJARAN NEMBANG PUPUH SUNDA DI SMP - Apon Gustana Rodia R; Dirgantara Wicaksono (Taksasila Edukasi Insani, 2025)
This research aims to develop a deep learning-based instructional model to enhance students’ skills in performing nembang pupuh Sunda, a traditional Sundanese vocal art form. The study was conducted at SMP Muhammadiyah Cianjur using the Research and Development (RD) method, following the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The product developed was an interactive mobile-based application equipped with AI-driven features for real-time voice analysis and feedback on pitch, tempo, and expressiveness. Data collection involved validation from media and content experts, teacher and student assessments, and pretest-posttest evaluation to measure learning outcomes. The model showed high feasibility and effectiveness in improving students’ vocal skills in nembang pupuh Sunda, with an N-Gain score indicating a significant increase in performance. This study demonstrates that integrating artificial intelligence with traditional arts education can foster student engagement, autonomy, and appreciation of local culture in a modern, technology-driven context. The findings offer valuable insights into preserving cultural heritage through innovative, student-centered learning approaches using deep learning technology.Keywords : Artificial intelligence, cultural education, deep learning, nembang pupuh, Sundanese music